Bandwidth enhanced deltoid leaf fractal antenna for 5.8 GHz WLAN applications - Rani Rudrama Kodali; Polepalli Siddaiah; Mahendra Nanjappa Giri Prasad (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
A wideband deltoid leaf fractal antenna is proposed for 5.8 GHz commonly used in industrial scientific and medical (ISM) and wireless local area networks (WLAN) applications. A microstrip patch antennas is designed with leaf shape radiating element. Using a leaf shape, it is possible to increase the perimeter of a design and thus reduce the overall dimensions of the antenna. A circular ring slot is made on the leaf shaped radiator, in a way that a circular disc is loaded at centre. Triangular fractal slots are made inside the circular disc to make it miniaturized. A partial ground is maintained with slot at centre. The antenna is fed by micro-strip feed. The locality and measurements of the fractal slots are varied to make the antenna radiate at 5.8 GHz with wider bandwidth (BW) of (2.26 GHz). The complete size of the antenna is 40 mm3 × 40 mm3 × 1.6 mm3. The step-by-step implementation of the antenna and the effects of its dimensions are compared and presented using the reflection coefficient curve. The measured reflections coefficient |S11|<-10 dB maintained the operational band from (5.36 GHz - 7.62 GHz), with gain 4.2 dBi. The proposed antenna is planned and simulated using high frequency structure simulator (HFSS). The simulated and measured comparison showed good agreement, the designed antenna is suitable for 5.8 GHz WLAN applications with wider bandwidth requirements.